2021
DOI: 10.1016/j.ijid.2021.07.010
|View full text |Cite
|
Sign up to set email alerts
|

Diagnostic accuracy of a SARS-CoV-2 rapid antigen test in real-life clinical settings

Abstract: Background Laboratory tests are a mainstay in managing the COVID-19 pandemic, and high hopes are placed on rapid antigen tests. However, the accuracy of rapid antigen tests in real-life clinical settings is unclear because adequately designed diagnostic accuracy studies are essentially lacking. Objectives We aimed to assess the diagnostic accuracy of a rapid antigen test to diagnose SARS-CoV-2 infection in a primary/ secondary care testing facility. Metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
73
2
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 103 publications
(80 citation statements)
references
References 10 publications
(21 reference statements)
3
73
2
2
Order By: Relevance
“…For example, Linares et al (13) reported that patients with less than seven days of symptoms showed a high viral load and a sensitivity of 86.5%, while the sensitivity dropped to 53.8% in asymptomatic patients or lower viral loads using the Panbio COVID-19 Ag Rapid Test Device (Abbot). The same effect was observed using the SD Biosensor-STANDARD Q COVID-19 test, where a sensitivity of 65.3% was observed in symptomatic patients and 44% in asymptomatic patients (14). Krüttgen et al ( 6) using the rapid SARS-CoV-2 antigen test from the Roche manufacturer, indicated that the sensitivity of the assay in 75 NPSs is 100% (Cq≤25), 95% (Cq≤30), 44.8% (Cq≤35), and 22.2% (Cq>35) compared to RT-qPCR.…”
Section: Discussionsupporting
confidence: 70%
“…For example, Linares et al (13) reported that patients with less than seven days of symptoms showed a high viral load and a sensitivity of 86.5%, while the sensitivity dropped to 53.8% in asymptomatic patients or lower viral loads using the Panbio COVID-19 Ag Rapid Test Device (Abbot). The same effect was observed using the SD Biosensor-STANDARD Q COVID-19 test, where a sensitivity of 65.3% was observed in symptomatic patients and 44% in asymptomatic patients (14). Krüttgen et al ( 6) using the rapid SARS-CoV-2 antigen test from the Roche manufacturer, indicated that the sensitivity of the assay in 75 NPSs is 100% (Cq≤25), 95% (Cq≤30), 44.8% (Cq≤35), and 22.2% (Cq>35) compared to RT-qPCR.…”
Section: Discussionsupporting
confidence: 70%
“…Despite limited sensitivity, the easy-to-perform antigen tests are of great interest where NAAT is unavailable, where prolonged turnaround time (TAT) precludes clinical utility or when it offers a cost-effective solution alternative to RT-PCR. Automated antigen assays have another advantage of high throughput screening possibility, however they had relatively long TAT compared to RAT [ 3 , 9 , 13 , 19 ]. Thereby, further strategies should therefore be evaluated to appropriately position these tools in the diagnostic context.…”
Section: Discussionmentioning
confidence: 99%
“…Previous publications have identified the sensitivity and specificity of other antigen-detection methods, including a meta-analysis of 29 studies on rapid antigen tests that indicate overall pooled sensitivity and specificity as 68% and 99% [ 38 ], and a recent large-scale study on a rapid antigen test (Roche/SD Biosensor) has shown similar diagnostic accuracy with 65% sensitivity and 100% specificity [ 39 ]. The immunofluorescence assay yields comparable sensitivity of 59% and specificity of 98%, owing to cross-reactivity with SARS-CoV.…”
Section: Discussionmentioning
confidence: 99%